Perjudian Dalam Sudut Pandang Hukum Perdata - Sagala, Fariz Eben Ezel; Mahmudah, Siti (Fakultas Syariah INSURI Ponorogo, 2023)
A person certainly has bad traits, one of the bad traits is that in the case of gambling, psychologically he is more afraid of the reality that will be faced when dealing with the police than of the punishment that will be imposed by the judge if he is caught in the act. Gambling according to Islamic law does not receive heavy sanctions such as intentional murder or adultery. Although gambling is still a sin for the perpetrators. The aim of this research is to compare the criminal provisions for gambling perpetrators in terms of positive Indonesian criminal law with Islamic criminal law. This research method is normative legal research, namely conducting a study of literature related to the research object. The criminal provisions for gambling players viewed from the positive criminal law aspect are that the criminal threat for online gambling players is heavier when compared to conventional gambling players. The criminal provisions for gambling perpetrators viewed from the aspect of Islamic law are that there are great sins and several benefits for humans, but the sins are greater than the benefits. At this time, everyone has the potential to gamble online. Thus, a special approach is needed from a religious perspective to prevent these unlawful acts